Impact and Response: Christianity and the Transformation of Legal Authority in Late Qing China - HAN , Xiangchen (Journal of Research for Christianity in China (JRCC), 2025)
Since its introduction to China, Christianity has been subject to regulation by Chinese legal authority. However, as Christian influence expanded within China—particularly since 1840—it exerted a profound impact on the evolution of Chinese legal systems. On one hand, missionaries and missionary activities severely disrupted the legal order of traditional Chinese society, inflicting suffering upon the populace. On the other hand, missionary work and the introduction of new ideas objectively played a certain positive role, accelerating the modernization of Chinese law.